Methodology for Model-Based Design of Mobile Robots Control Algorithms - М. М. Tatur; М. S. Ihnatsiuk; А. D. Konikov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
This article proposes the formalized methodology for model-based design of mobile platform management systems. The methodology is based on an alternative approach to development, when the model of controlled object is firstly created as a design tool, and then control algorithms are developed. This allows to find the most successful algorithms and select control parameters that are close to optimal in the process of model-based design. As examples, two typical tasks from the field of mobile platform management are given - braking and steering control. The proposed methodology has sufficient unification to be used in the design of control systems for mobile platforms of various types, with different positioning systems, principles of navigation and autopiloting.